Structural and optical characterization of As-grown and annealed ZnxCd1-xS thin-films by CBD for solar cell applications - Ahamed E.M.K.I.; Das N.K.; Gupta A.K.S.; Khan M.N.I.; Matin M.A.; Amin N. (International Journal of Renewable Energy Research, 2023)
Absorption spectroscopy; Annealing; Binary alloys; Buffer layers; Crystallinity; Deposition; Energy gap; Morphology; Optical films; Optical properties; Semiconductor alloys; Structural properties; Surface morphology; Thin film solar cells; X ray diffraction; Zinc; Annealing; As-grown; As-grown films; Chemical-bath deposition; FESEM; Thin-films; UV-vis-NIR; XRD; Zinc content; Znxcd1-xS; Thin films